Cantilever-enhanced photoacoustic measurement of HTO in water vapor - Juho Karhu; Markus Nyman; Marja Siitari-Kauppi; Tuomas Hieta (Photoacoustics, 2023)
A photoacoustic detection of tritiated water (HTO) is presented. The method uses cantilever-enhanced photoacoustic spectroscopy (CEPAS) to reach sub-ppb sensitivity for HTO in the gas phase. A noise equivalent concentration of 0.88 ppb is reached with a sampling time of 1 min. The high performance and small sample volume of CEPAS allows sensitive detection of HTO from a sample with low total activity.